Investigating Domestic Tourists’ Perception of Service Attributes in Indoor Tourist Destination - Anisa Zahwa Akbara; Hubertina Karolina Ngarbingan (Yayasan Riset dan Pengembangan Intelektual, 2023)
The tourism industry must be able to adapt to new services in the new normal era and work to regain the trust of tourists who have been subjected to unfavorable conditions since the Covid 19 pandemic. Tourism must be prepared to adapt to new services in the industry in the new normal era and work to regain the trust of tourists. This study aims to examine the importance-performance of service quality attributes and satisfaction of domestic tourists in indoor tourist destination using quantitative descriptive with the Importance Performance Analysis (IPA) technique. A total of 162 domestic tourists from Jakarta Aquarium and Safari were the sample in this study. Data was collected using questionnaire that consist of three attributes and includes 18 service items. The results of the analysis show that of the 18 service items tested, there are five service items that are considered important and show high satisfaction from tourists. Meanwhile, there are four items that are also considered important but show performance that makes tourists dissatisfied. This study demonstrates the relevance of tourist feedback in evaluating service characteristics at tourist destinations. This research provides a framework for developing effective marketing strategies for tourist destinations, especially indoor tourist destinations. When these services meet the needs and wants of tourists, they can generate positive reviews or promotions and act as advocates for these tourist destinations.